2009
DOI: 10.3945/jn.109.104901
|View full text |Cite
|
Sign up to set email alerts
|

Selenoprotein Gene Expression in Thyroid and Pituitary of Young Pigs Is Not Affected by Dietary Selenium Deficiency or Excess

Abstract: Expression and function of selenoproteins in endocrine tissues remain unclear, largely due to limited sample availability. Pigs have a greater metabolic similarity and tissue size than rodents as a model of humans for that purpose. We conducted 2 experiments: 1) we cloned 5 novel porcine selenoprotein genes; and 2) we compared the effects of dietary selenium (Se) on mRNA levels of 12 selenoproteins, activities of 4 antioxidant enzymes, and Se concentrations in testis, thyroid, and pituitary with those in liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
92
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(108 citation statements)
references
References 54 publications
12
92
4
Order By: Relevance
“…Alterations of these factors were associated with expressions of 12 selenoproteins (1,3,5,9,18,19). However, to the best of our knowledge, there was no information on effects of dietary selenium, in particular high selenium intake, on body protein metabolism, although protein synthesis was reported to negatively regulate insulin sensitivity (20,21) and a high protein diet inhibited the development of type 2 diabetes (22).…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Alterations of these factors were associated with expressions of 12 selenoproteins (1,3,5,9,18,19). However, to the best of our knowledge, there was no information on effects of dietary selenium, in particular high selenium intake, on body protein metabolism, although protein synthesis was reported to negatively regulate insulin sensitivity (20,21) and a high protein diet inhibited the development of type 2 diabetes (22).…”
Section: Introductionmentioning
confidence: 82%
“…As shown in our previous studies (3,18), the high-selenium diet resulted in a moderate (20-50%) increase in GPX activities in both liver and muscle. Overproduction of GPX activity by Gpx1 overexpression in mice led to type 2 diabetes-like phenotypes, including hyperlipidemia and fatty liver (1,9,19), and the selenium deficiency partially rescued those disorders (9).…”
Section: Discussionmentioning
confidence: 99%
“…A number of other studies in various species reported that >75% of selenoprotein transcripts examined were downregulated significantly by selenium deficiency when just a selenium-deficient and a selenium-adequate group were compared (47)(48)(49)(50), and several reported that the majority of selenoprotein transcripts examined were downregulated significantly by selenium deficiency when 3 groups (selenium-deficient, seleniumadequate, high-selenium) were studied (51,52). In contrast, when multiple levels of selenium supplementation were used, resulting in well-defined biomarker plateaus, far fewer selenoprotein transcripts were significantly altered by selenium deficiency (20), especially in avian studies that used commercial (outbred) strains (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…While Zhou et al [116] found little effect of dietary Se concentrations (0.02, 0.3, and 3.0 mg/ kg diet) on mRNA levels of 12 selenoprotein genes in thyroid, pituitary, liver, or muscle, Liu et al [62] reported that mRNA expression of the remaining 13 selenoproteins in 10 tissues of pigs responded to dietary Se in three patterns. But, there was no common regulation for any given gene across all tissues or for any given tissue across all genes [62].…”
Section: High Se Intake On Tissue Redox Status and Selenoprotein Exprmentioning
confidence: 99%
“…This antioxidant effect was in accordance with increased plasma GPx3 activity by high Se over adequate Se supplements, although the high selenite diet had no effect on the activities of GPx1 and SOD in the liver, and even decreased catalase activity. Using the Se-enriched yeast [116], Zhou et al have demonstrated that 3.0 mg of Se/ kg of diet enhanced (43-88%) GPx activity among four tissues of pigs (liver, testis, thyroid, and pituitary) compared to those fed 0.3 mg of Se/kg of diet. However, the high Se diet did not affect activities of plasma GPx3 and other three antioxidant enzymes in any of the four tissues.…”
Section: High Se Intake On Tissue Redox Status and Selenoprotein Exprmentioning
confidence: 99%